Role of brain derived neurotropic factor in obesity. (March 2020) - Pandit, Mahashweta; Behl, Tapan; Sachdeva, Monika; Arora, Sandeep
Abstract: Purpose: Correlating abasement in brain derived neurotrophic factor (BDNF) and cognated energy homeostasis together with obesity and metabolic syndrome in both human and animal models. In this review, we focus on the evidence for BDNF as regulator of satiety and body weight; analysing the latest evolvement of BDNF functions via the help of published research results, data and meta-analysis. Key findings: Neurotrophic factors such as BDNF and CNTF are essential for body weight management. Mutations in the gene of BDNF and impairment of activation of its receptor TrkB results in austere obesity, insatiable appetite and less energy expenditure. Severe obesity was found to cause BDNF haploinsufficiency and it is the foundation for hyperphagia and obesity linked with some patients with the Wilms' tumor, aniridia, genitourinary disorders, and mental retardation (WAGR) syndrome. The WAGR syndrome is an infrequent disease and repercussions from two distinct alleles of this specific gene, sporadically dimensioned, interconnecting deletions on chromosome 11 that extend into the BDNF gene in few of the investigated cases. Conclusion: The current article reviews the sophisticated resemblance of BDNF in obesity and the consequences of BDNF gene in metabolic disorders. The cytoprotective action of BDNF clearly explains its role other neurological diseases as well where the basic mechanism involved is protection of neuronal cells. BDNF faces a limitation in clinical administration due to its lower bioavailability, shorter half-life and poor penetrability through blood brain barrier. Highlights: BDNF plays an intricate role on obesity. BDNF cause alteration in plasma glucose, insulin and lipid levels. BDNF does not present changes in inflammatory markers in obesity.